A.L.N Interesting Store / Alan James - James, Alan (2021)
This assignment also known as Social Media Portfolio which is one of Principles of Entrepreneurship (ENT530) assignment. From this Social Media Portfolio assignment, I was entrusted to create a online business and promoting the business by using social media as a online purchase platform. Moreover, I choose arts and musics business which is I sell musical instruments such as guitar, electric guitar, piano, drum and amplifier through Facebook page. By selling musical instruments, I can offer the best brand of the musical instruments to the buyers or customers. My business located at Karamunsing Complex, Kota Kinabalu, Sabah because the located place has a very strategic place that can attract people around there. The business location is important because it can make the customers easier to reach the product and prefer what kind of musical instruments brand that they like. Moreover, it could give a lot of profits to my business. My target customers is for those who like to play musical instruments as hobby and also for those who would like to established a music band. This facebook page help boost my business profits and can gain attraction from the customers. By selling these musical instruments, it can help customers to liven their hobbies to play musical instruments. My business sells various brand of musical instuments to help people or customers to choose what brand that they prefer or more suitable.